Colitis up-regulates local glucocorticoid activation and down-regulates inactivation in colonic tissue - Bryndová, J; Zbánková, S; Kment, M; Pácha, J (Scandinavian journal of gastroenterology, 2004)
BACKGROUND: Pro-inflammatory processes are counteracted by anti-inflammatory factors such as glucocorticoids. The response of target cells to glucocorticoids depends on several factors including prereceptor modulation of glucocorticoid signals via local glucocorticoid metabolism. This is determined by two isoforms of 11beta-hydroxysteroid dehydrogenase (11betaHSD); 11betaHSD1 operates in vivo as a reductase converting inactive 11-oxo glucocorticoids to active glucocorticoids cortisol or corticosterone, whereas 11betaHSD2 catalyses oxidation of active glucocorticoids to their inactive 11-oxo derivatives. The aim of this study was to investigate the changes in local metabolism of glucocorticoids and in the expression of 11betaHSD1 and 11betaHSD2 mRNA during colonic inflammation. METHODS: Acute colitis was induced by intracolonic administration of 2,4,6-trinitrobenzenesulphonic acid (TNBS) or by drinking a dextran sodium sulphate (DSS) solution. Metabolism of glucocorticoids was measured in tissue fragments in vitro and 11betaHSD1 and 11betaHSD2 mRNA abundance was quantified using real-time RT-PCR one week after administration of TNBS and 10 days after drinking the DSS solution. RESULTS: In both models of inflammatory bowel disease we observed down-regulation of corticosterone oxidation to 11-dehydrocorticosterone by 64% (TNBS) and 53% (DSS) and reciprocal stimulation of reduction of 11-dehydrocorticosterone to corticosterone by 83% and 54%, respectively. A similar pattern was observed at the level of mRNA; 11betaHSD1 mRNA was significantly higher (TNBS: increase by 660%; DSS: increase by 760%) and 11betaHSD2 mRNA lower (TNBS: decrease by 85%; DSS: decrease by 60%) during inflammation. CONCLUSIONS: Colitis induces local glucocorticoid activation from 11-oxo steroids and decreases glucocorticoid inactivation; i.e. inflammation increases local tissue ratio of active and inactive glucocorticoids. The results indicate that the changes in local metabolism of glucocorticoids could contribute to the control of an overshoot of inflammation processes in the colon.
Keywords: ulcerózní kolitida; Crohn Disease; 11-beta-hydroxysteroiddehydrogenasa typ 1; modely nemocí na zvířatech; RNA, Messenger; Male; Rats, Wistar; Corticosterone; 11-beta-Hydroxysteroid Dehydrogenase Type 2; 11-beta-hydroxysteroiddehydrogenasa typ 2; Crohnova nemoc; 11-beta-Hydroxysteroid Dehydrogenase Type 1; mužské pohlaví; potkani Wistar; krysa rodu Rattus; Trinitrobenzenesulfonic Acid; Animals; Dextran Sulfate; kortikosteron; zvířata; Rats; Disease Models, Animal; Colitis, Ulcerative; kyselina trinitrobenzensulfonová; messenger RNA; síran dextranu